The Effect of Gradual Training By Decreasing Training Load On Some Physical, Physiological Variables, and Achievement In Youth Weightlifters - Hashim Fenjan, Falih; Ahmed Saeed, Taiseer; Khalid Yasse, Omar (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to prepare a curriculum on the principle of gradual decrease the intensity and size training and its impact on some variables , physical, physiological and achievement of powerlifting youth The research problem is represented in the great effort that is facing the players during the tournament , which causes fatigue due to overload in training before the competition, leading to a lack of Achievement and failure of the lifts and sometimes to The researchers used the experimental approach with the two experimental groups. The first experimental group underwent a drop in training intensity from three peaks per week to one peak to be of the same weight, and the second experimental group underwent a gradual decrease in size by reducing the number of iterations while maintaining Training stresses. As the same exercises were applied for the two experimental groups, the researcher concluded that the first experimental group achieved better results than the second experimental group.